Isolation and Characterization of Pathogens Responsible for Urinary Tract Infection in Bangladesh and Determination of their Antibiotic Susceptibility Pattern - Saima Mollick, Tumpa Dasgupta, Md. Jabir Hasnain, Mushtaque Ahmed (Journal of Applied Pharmaceutical Science, 2016)
The aim and objectives of this study were to determine the etiological pathogens of the Urinary Tract Infection and to determine their antibiotic sensitivity pattern in Bangladesh. This study was carried out on clinically suspected UTI patient in a Private Diagnostic Centre, Bangladesh from May 2015 to November 2015. From total 200 urine samples, pathogens were isolated and identified and their antibiotic susceptibility was observed by standard microbiological procedures. Out of 200 urine samples 124 (62%) patients tested positive for culture. In gram negative bacteria, the most predominant was the E. coli (48.39%) followed by Klebsiella spp (14.52%), Pseudomonas spp (3.23%) and Acinetobacter spp (3.23%). In the gram positive bacteria Staphylococcus aureus (13.71%) and Enterococcus spp (11.29%) were found. Occasionally Candida spp. (5.65%) was found. Gram-negative bacteria were more sensitive to Imipenem, Amikacin and Nitrofurantoin. On the otherhand Gram-positive bacteria showed their sensitivity to Amoxicillin-clavulinic acid and Linezolid and Vancomycin showed 100% sensitivity. UTI has become difficult to treat due to appearance of pathogens with increasing resistance to antimicrobial agents. This study showed that pathogens responsible for UTI showed increasing resistance to the commonly prescribed drugs that in turn leaves very few alternative options for the treatment of UTIs.
Keywords: Urinary Tract Infection, Sensitivity, E.coli, Staphylococcus aureas, Nitrofurantoin, Vancomycin.